INVESTIGASI Bacillus cereus DAN Salmonella PADA NASI GORENG PEDAGANG KAKI LIMA DI SEKITAR KAMPUS UNIVERSITAS JEMBER - Eka Ruriani; . Nurhayati (JURNAL AGROTEKNOLOGI, 2010)
Food safety in fast food is very important to be observed, since it is potential to cause the incidence of food borne diseases. This research investigated the presence of two pathogenic microorganisms that are Bacillus cereus and Salmonella in fried rice, as one of fast food sold by street vendor around Jember University campus. The sampling was done three times at five location for every two hours started at six pm until ten pm in temperature 25-280C and RH 55-66%. The media used in this investigation were MYP for B. cereus and some media (LB, SSA, BSA, SCB, TSIA, and LIA) for Salmonella. The result founded that seven samples contamined by B. cereus, four samples contamined by Salmonella (S. parathypimurium B or C) and three samples contamined by another pathogens which were suspected as Yersinia enterolitica or Vibrio cholerae.Keywords: Bacillus cereus, food borne disease, fried rice, Salmonella